Pelatihan Pengembangan Produk Kreatif dari Rotan pada IKM di Jombang dengan Pelibatan Masyarakat - Gunawan Gunawan; Guguh Sujatmiko; Dudi Anandya (University of Merdeka Malang, 2021)
In moving towards adapting to new habits during the COVID-19 pandemic, efforts to revive the economy from small and medium-sized enterprises (SMEs) are essential. UD. Delima Jaya, a small wood-furniture firm in Catak Gayam Village, Mojowarno, Jombang regency, targets the local-product development program. The SME empowerment intervention principle consists of 3 elements: Market Needs - Supply chain networks - Internal Capabilities. This principle is applied to an activity program by supporting partners in exploring market needs, selecting new products to be developed, establishing partnerships that form supply chains, involving community members as production partners, enhancing production capabilities, and supporting marketing products personally and creatively. This method has been applied by obtaining market demand for wood and rattan combination products, getting partners for marketing, and bringing partners with production expertise. The training was held for 1 week in July 2020 at PPPUD partner locations by involving local women, with two instructors from outside Jombang. The training results show the fast mastery of skills among the participants and the quality of products made. This program helps SMEs and the community to rise in economic activities.DOI: https://doi.org/10.26905/abdimas.v6i1.4852